1989
DOI: 10.1021/tx00012a011
|View full text |Cite
|
Sign up to set email alerts
|

Formation of acyclic and cyclic guanine adducts in DNA reacted with .alpha.-acetoxy-N-nitrosopyrrolidine

Abstract: This paper describes the reaction of alpha-acetoxy-N-nitrosopyrrolidine with DNA to produce six adducts: two new acyclic adducts, 7-(4-oxobutyl)guanine (6) and 7-(3-carboxypropyl)guanine (7), and four cyclic adducts--the exocyclic 7,8-guanine adducts 5, 11, and 12 and an exocyclic 1,N2-guanine adduct 13--which we have previously characterized. The initial purpose of this study was to carry out an independent synthesis to verify the structure of adduct 5, which is formed in liver DNA of rats treated with N-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 8 publications
5
54
2
Order By: Relevance
“…The ylide intermediate 14 may be more stable in Guo than in dGuo although comparative studies of such intermediates do not appear to have been reported. In support of the mechanism proposed in Scheme 3, we have observed that when DNA containing adduct 9 is treated with NaOH, adduct 9 disappears with a corresponding increase in levels of cyclic adduct 8; 2 however, this reaction does not occur under neutral conditions at 37 or 100 °C (14,15). Further studies are required to investigate the mechanisms associated with the higher levels of cyclic adduct 8 as a product of the reaction of R-acetoxyNPYR with Guo compared to dGuo.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The ylide intermediate 14 may be more stable in Guo than in dGuo although comparative studies of such intermediates do not appear to have been reported. In support of the mechanism proposed in Scheme 3, we have observed that when DNA containing adduct 9 is treated with NaOH, adduct 9 disappears with a corresponding increase in levels of cyclic adduct 8; 2 however, this reaction does not occur under neutral conditions at 37 or 100 °C (14,15). Further studies are required to investigate the mechanisms associated with the higher levels of cyclic adduct 8 as a product of the reaction of R-acetoxyNPYR with Guo compared to dGuo.…”
Section: Discussionmentioning
confidence: 58%
“…In the reactions with dGuo, adduct 9 was formed up to 3 times more extensively than was the cyclic adduct 8 (17). In reactions with DNA, adduct 9 was produced in quantities about 60% as great as the cyclic adduct 8 (15). Although adduct 9 was not quantified in the reactions of R-acetox-yNPYR with dGuo in this study, our previous work indicates that the total levels of adducts 8 and 9 in the reaction with dGuo would approach the amount of cyclic adduct 9 seen in the reaction with Guo (17).…”
Section: Discussionmentioning
confidence: 98%
“…When the separated adduct was allowed to decompose in the HPLC effluent at 37 °C, a stable product resulted that readily partitioned into ethyl acetate. The FAB/MS data (Table ) confirms that this compound is a guanine adduct of the quinone methide, and the UV and 1 H NMR data (Tables and ) are constant with the spectra of 7-alkylguanines ( ). In particular, the C-8 proton at 8.05 ppm falls within the 7.90−8.48 ppm range for some other 7alkylated derivatives.…”
Section: Resultsmentioning
confidence: 64%
“…NPYR is metabolically activated via alpha‐hydroxylation by cytochrome P450 enzymes to yield reactive intermediates, 4‐hydroxybutylaldehyde, and crotonaldehyde [41]. These metabolites can alkylate deoxyguanosine, and mainly result in exocyclic adducts such as N 7 ,C‐8 guanine adducts and 1, N 2 ‐propanodeoxyguanosine [42]. Because these adducts have also been found in DNA from tissues of NPYR‐ or crotonaldehyde‐treated animals, they might be expected to be the major adducts formed in vivo [43,44].…”
Section: Discussionmentioning
confidence: 99%